Development of partially simulated chemical reactor for the implementation of advanced control systems - Wahab, Ahmad Khairi Abdul; Hussain, M.A.; Omar, R. (2009)
In this work, a partially simulated exothermic chemical reactor (PARS-EX) pilot plant available in our department is designed and utilized to implement and test various conventional and advanced control strategies. In this reactor, an exothermic chemical reaction is simulated, where heat energy generated from the reaction is replaced by a calculated and controlled steam flow rate through a coil immersed in the reactor. A control valve is used to regulate flow rate of fresh water into a heat exchanger. The heat exchanger then cools the process fluid and recycles it back to the reactor, hence controls the temperature of the reactor. Prior to the online implementation, several advanced controllers are simulated for tracking required temperature of the reactor. The online advanced control results are made possible due to the developed customized graphical user and process interface. The work also highlights the software development involved. The software is designed so that it is capable of implementing several advanced nonlinear control strategies such as genetic algorithm and fuzzy logic.